PENGAWASAN DINAS PENDIDIKAN PADA PENGELOLAAN DANA BANTUAN OPERASIONAL SEKOLAH DI KECAMATAN PINOLOSIAN KABUPATEN BOLAANG MONGONDOW SELATAN - TADDI, INDRA LESMANA; TAMPI, GUSTAAF; KOLONDAM, HELLY (JURNAL ADMINISTRASI PUBLIK, 2020)
The purpose of this study is to find out and describe how the supervision of the education department inthe management of school operational assistance funds in Pinolosian Subdistrict, Bolaang Mongondow SelatanDistrict. The research method used in this research is descriptive research method with a qualitative approach.Data collection in this study was carried out through interviews, observations and document collection. While thedata analysis techniques that researchers use are qualitative with the Lexy J. Moleong descriptive approach. Basedon research results Problems that arise in the management of BOS funds are weak oversight of related agencies inthis case the Office of Education. Providing School Operational Assistance funds that are not on target is wastingmoney because it can lead to misappropriation, to prevent this, involving the community must oversee theimplementation and distribution of BOS.a conclusion can be drawn that the function of monitoring BOS funds bythe Education Office and the Management Team of South Bolaang Mongondow Regency is carried out well onlyit needs to be maximized. There are a number of deviations done by the schools in the form of a discrepancy in theaccountability report with the reality in the field and there are some schools that do not follow the technicalguidelines in the form of no information boards on the use and management of BOS funds in schools. Errors ordeviations in the implementation or use of BOS funds at schools, the District Management Team gives a warningand carries out / corrects or corrects.Keywords : measure, compare, correction / corrective actions